2018
DOI: 10.1051/matecconf/201815005037
|View full text |Cite
|
Sign up to set email alerts
|

Overall Equipment Efficiency (OEE) Enhancement in Manufacture of Electronic Components & Boards Industry through Total Productive Maintenance Practices

Abstract: In an environment of intense global competition, both creative and proven strategies need to be considered in order to bring about the effectiveness and efficiency in manufacturing operation. Total Productive Maintenance (TPM) is one of the effective maintenance strategy in enhancing the equipment effectiveness and to achieve a significant competitive advantage. This research paper addresses the impact of three TPM pillars namely planned maintenance (PM), autonomous maintenance (AM) and focused maintenance (FM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 8 publications
0
13
0
7
Order By: Relevance
“…It usually seeks to maximize the effectiveness of the equipment during its entire life. TPM consists of three words (Fam et al, 2018); Total: means involving the entire workforce from top to bottom in equipment maintenance. Productive: means to ensure that the operation is efficient maintenance problems/ costs.…”
Section: Overall Equipment Effectiveness (Oee)mentioning
confidence: 99%
See 1 more Smart Citation
“…It usually seeks to maximize the effectiveness of the equipment during its entire life. TPM consists of three words (Fam et al, 2018); Total: means involving the entire workforce from top to bottom in equipment maintenance. Productive: means to ensure that the operation is efficient maintenance problems/ costs.…”
Section: Overall Equipment Effectiveness (Oee)mentioning
confidence: 99%
“…The efficiency of the assembly line was increased from the value targeted by the company using the OEE approach. The impact of implementation of three pillars of TPM in a die attached equipment in a semiconductor industry was addressed in a study (Fam et al, 2018) in which a pair mean analysis was carried out for finding the impact of TPM elements and OEE and it was observed that there is a significant increase in the OEE level of the plant due to which the productivity and quality of the products are also improved to a very large extent. A new performance ratio strategy has been used in a study (Keyser & Sawhney, 2013) to improve the OEE of the plant by cycle time limitation reduction.…”
Section: Overall Equipment Effectiveness (Oee)mentioning
confidence: 99%
“…[18] Electronic Industry The result of quality assessment is 95.76% -96.11%. [19] Electronic Industry Increased value of OEE seven month [20] Service Industry Value of the effectiveness of the three machines SOLNA WEB can be known through the OEE calculations has been done, until it gets results with a mean value on SOLNA WEB machine [21] Electronics Industry OEE analysis large losses were obtained reduce the speed loss [22] Drug Industry Increase productivity in blistering machines succeeded in increasing OEE from 49.05% to 64.05% [23] Services Industry The value of painting services of availability is 95.33%, the performance value is 76.2%, the quality is 97.4%. [24] Food and Beverage Industry Human error in maintenance has a significant positive relationship with OEE [25] Electronics Industry OEE increased from 45.36% to 60.38%.…”
Section: [9]mentioning
confidence: 99%
“…Therefore, automation can help SMEs in food manufacturing industry to improve the product quality follow by increasing the reputation and market value of the company. On top of that, to maintain the automotive and machineries performance, SMEs should look into lean manufacturing, overall equipment efficiency and total productive maintenance practice as discussed in [35], [36].…”
Section: To Improve the Product Qualitymentioning
confidence: 99%